Safety and efficacy of a feed additive consisting of an essential oil derived from fresh leaves of Melaleuca cajuputi Maton & Sm. ex R. Powell and Melaleuca leucadendra (L.) L. (cajuput oil) for use in all animal species (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; Alena Pechová; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of cajuput oil obtained from fresh leaves of Melaleuca cajuputi Maton & Sm. ex R. Powell and Melaleuca leucadendra (L.) L., when used as a sensory additive for all animal species. The FEEDAP Panel concluded that cajuput oil is safe up to the maximum proposed use levels in complete feed of 30 mg/kg for sows and dogs, 50 mg/kg for horses and ornamental fish, 40 mg/kg for salmon and 5 mg/kg for cats. For the other species, the calculated safe concentrations were 18 mg/kg for chickens for fattening, 26 mg/kg for laying hens, 23 mg/kg for turkeys for fattening, 37 mg/kg for pigs for fattening, 31 mg/kg for piglets, 78 mg/kg for veal calves (milk replacer), 69 mg/kg for cattle for fattening and sheep/goats, 45 mg/kg for dairy cows and 28 mg/kg for rabbits. These conclusions were extrapolated to other physiologically related species. For any other species, the additive is safe at 5 mg/kg complete feed. The use of cajuput oil in water for drinking was considered safe provided that the total daily intake does not exceed the daily amount considered safe when consumed via feed. No concerns for consumers and the environment were identified following the use of the additive up to the highest safe use level in feed. The essential oil under assessment should be considered as an irritant to skin and eyes, and as a dermal and respiratory sensitiser. Since cajuput oil was recognised to flavour food and their function in feed would be essentially the same as that in food, no further demonstration of efficacy was considered necessary.